Pengaruh Partisipasi Anggaran Terhadap Kinerja dengan Kepercayaan Sebagai Variabel Mediasi (Studi Kasus pada PT PLN Persero) - Dwi Ichwan Kurniawan; SeTin SeTin (Universitas Kristen Maranatha, 2021)
Abstract The objective of this research is examine managerial trust on mediating the effect of budget participation on job performance. The population of this research were all low level manager that works in National Electricity Company. Purposive sampling is used to conduct the sample of the research. This research used questionnaires as data collections tools, and distribute on 103 respondent. The data collected were processed by SPSS 25.0 with path analysis using Simple Linear Regression and Modified Regression Analysis (MRA). This research found budget participation positive effect on managerial trust and managerial trust positive effect on job performance but managerial trust not mediating the effect of budget participation on job performance. Keywords: Budget Participation, Job Performance, and Managerial Trust